Quality and Longevity of Local Ram’s Sexed Sperm with Albumin Colums - Nurcholidah Solihati; Siti Darodjah Rasad; Annisaa Yusrina; Kikin Winangun; Toha . (Jurnal Ilmu Ternak, 2019)
Sperm sexing applications can support the effectiveness of artificial insemination (AI) programs in sheep. The albumin column method is one method of sperm sexing that is relatively easy and inexpensive compared to other methods, but research needs to be done to obtain a method that results in the quality and longevity of sexed sperm that is feasible to use for AI programs, one of which is by searching for incubation or sexing time. This study used 10 ejaculate semen from two local sheep around 2-3 years old. We used bovine serume albumin (BSA) as the albumin column with two fractions which is 5% in the upper fraction and 10% in the lower fraction. The treatment given was three lengths of incubation/sexing time (45, 60 and 75 minutes) which were repeated 10 times. Parameters consist of the quality of semen (motility, abnormalities, intact plasma membrane, intact acrosome cup) and longevity. Data were analyzed by analysis of variance and Duncan's advanced test. The results showed that the length of sexing time had a very significant effect on the quality of semen, but the length of incubation/sexing time up to 75 minutes still produced the quality of semen that was qualify for AI. The result also showed that incubation/sexing time does not affect the longevity of sexed sperm. It was concluded that the quality of sexed sperm of local ram that sexing with albumin colums fulfilled the quality for artificial insemination and the incubation/sexing time for 45-75 minutes can be used to obtain the qualify sexed sperm for artificial insemination with chilled semen.